Responses to Yes/No Questions in Spanish by Chinese ELE Learners: A Cognitive-Contrastive Approach - Li, Haozhen (2026)
This study explores from a cognitive linguistics perspective the difficulties faced by Chinese learners of Spanish as a foreign language (ELE) when responding to yes/no questions. It particularly analyzes how interference from Mandarin Chinese cognitive logic affects responses in Spanish, leading to frequent errors. Through oral and written questionnaires, it was found that beginner students made more errors, while immersion experience significantly reduced these difficulties. The article concludes with pedagogical suggestions aimed at improving the teaching of affirmative and negative responses in Spanish for Chinese-speaking learners.